Natural Rubber Recycled Chloroprene Rubber Blends Preparation And Properties - Salleh, Siti Zuliana (2017)
The utilization of rejected rubber product from chloroprene rubber glove as a part of ingredient in rubber blend is a solution to reduce rubber waste in industry. In the first series, the effect of two different chloroprene rubbers; virgin and recycled denoted as vCR and rCR in natural rubber (NR) blends was studied. The properties of NR/vCR blends are generally higher than NR/rCR blends. In the second series, the NR/rCR blend is modified with natural rubber latex (NRL) as a solution to improve the adhesion between NR and rCR. The result showed that the addition of NRL improved the properties of NR/rCR blends especially the mechanical properties. The third series involved the variation of metal oxides ratios in order to obtain the optimum properties in NR/rCR blends. The addition of 4/10 (phr/phr) of magnesium oxide/zinc oxide (MgO/ZnO) into the rubber blend showed an optimum tensile strength. Meanwhile, the forth series involved the effect of various types and loading filler on the properties of NR/rCR blends. The addition of reinforced fillers such as carbon black or silica with coupling agent; (3-Aminopropyl) triethoxysilane (APTES) has improved the properties of NR/rCR blends. The addition of filler at lower loading improved the miscibility in NR/rCR blends. The addition of nonreinforced filler which is calcium carbonate did not showed significant effect in properties of NR/rCR blends. In the last series, different virgin rubber is used together with rCR. The result revealed that rCR is the most suitable to be blended with NR as compared to other rubbers; for example epoxidized natural rubber or styrene-butadiene rubber.